DARI TEACHER CENTERED KE STUDENT CENTERED: TRANSFORMASI PARADIGMA STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA - Isrul Rayu Saputra; M. Al Fajril Munir; Muhammad Risky Ihsan; Helmi Iskandar; Izzatul Fatyah Daulay; Nur Hafidhzah Arabella; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The dynamic development of the times demands a paradigm shift in religious education so that it no longer becomes trapped in monotonous, doctrinal-textual memorization methods, but instead transforms toward more meaningful learning. This study aims to analyze the urgency, forms of transformation, and impact of implementing the Student Centered Learning (SCL) strategy in reconstructing the quality of Religious Education learning in schools. The method used in this study is descriptive qualitative through a literature study approach and comparative conceptual analysis of relevant academic sources. The research results show that the implementation of SCL through problem-based learning, inquiry, and role-playing models has been proven to significantly enhance the internalization of religious values in a deep, autonomous, and contextual manner in students. In conclusion, the transformation from Teacher Centered Learning to Student Centered Learning is not merely a technical-methodological change, but an urgent philosophical necessity to shape students' character to be critical, tolerant, and possess a balanced sense of social piety in the modern era.